Pengembangan Buku Ajar Ide Pokok Berbasis Potensi Lokal Pantai Tambakrejo Menggunakan Model Scramble Untuk Siswa Kelas IV SD - Nicky Nadila; Sripit Widiastuti; Adin Fauzi (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This research aims to determine whether the Tambakrejo Beach Local Potential-Based Textbook can be used as main idea material in Indonesian language subjects. In this research, the RnD method is applied with seven stages: 1) Identification of problems and opportunities; 2) Data collection; 3) Product design; 4) Design validation; 5) Design revision; 6) Product testing; and 7) Product evaluation. To validate this book, subject, language and media experts and readability tests were carried out by teachers and students through questionnaires and interviews. The results show that this book is very worthy. 91.66% of expert validators assessed the coverage of material and language, media expert validation was 83.49%, and student and teacher readability validation was 100% and 92% respectively. Therefore, it can be concluded that Class IV Elementary School students can use this textbook as a source of learning Indonesian for Main Idea material. Thus, it is hoped that this book will encourage the strengthening of local culture in education and help students understand more contextual teaching.